Current knowledge for pyridoxine-dependent epilepsy: a 2016 update. Issue 1 (2nd January 2017) - Pena, Izabella Agostinho; MacKenzie, Alex; Van Karnebeek, Clara D.M.
ABSTRACT: Pyridoxine-dependent epilepsy (PDE) is a rare genetic condition characterized by intractable and recurrent neonatal seizures that are uniquely alleviated by high doses of pyridoxine (vitamin B6). This recessive disease is caused by mutations in ALDH7A1, a gene encoding Antiquitin, an enzyme central to lysine degradation. This results in the pathogenic accumulation of the lysine intermediates Aminoadipate Semialdehyde (AASA) and its cyclic equilibrium form Piperideine-6-carboxylate (P6C) in body fluids; P6C reacts with pyridoxal-5ʹ-phosphate (PLP, the active form of vitamin B6) causing its inactivation and leading to pyridoxine-dependent seizures. While PDE is responsive to pharmacological dosages of pyridoxine, despite lifelong supplementation, neurodevelopment delays are observed in >75% of PDE cases. Thus, adjunct treatment strategies are emerging to both improve seizure control and moderate the delays in cognition. These adjunctive therapies, lysine restriction and arginine supplementation, separately or in combination (with pyridoxine thus termed 'triple therapy'), have shown promising results and are recommended in all PDE patients. Other new therapeutic strategies currently in preclinical phase of study include antisense therapy and substrate reduction therapy. We present here a comprehensive review of current treatment options as well as PDE phenotype, differential diagnosis, current management and views upon the future of PDE research.